2014
DOI: 10.1080/00173134.2014.962079
|View full text |Cite
|
Sign up to set email alerts
|

Calcium distribution during pollen development ofUncaria hirsutaHavil. (Rubiaceae), with special reference to the function of the protruding oncus

Abstract: Calcium distribution in the developing anthers of Uncaria hirsuta was studied with the potassium pyroantimonite method. The amount and distribution of calcium precipitates change along with the developing anthers and pollen grains in U. hirsuta. Calcium distribution is closely correlated with the anther wall differentiation, exine and intine formations. In mature pollen grains, abundant calcium is in intine, protruding onci and nucleus. A generative cell has more calcium than a vegetative cell does. The calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition, lipidic material, which may be classed as pollenkitt (El-Ghazaly et al, 2001; Edlund et al, 2004), is deposited onto the exine surface at the late BCP stage. These ontogenetical features were also described in the available ultrastructural studies in Rubiaceae (Hansson and El-Ghazaly, 2000; El-Ghazaly et al, 2001; Kuang and Liao, 2015). …”
Section: Discussionmentioning
confidence: 58%
“…In addition, lipidic material, which may be classed as pollenkitt (El-Ghazaly et al, 2001; Edlund et al, 2004), is deposited onto the exine surface at the late BCP stage. These ontogenetical features were also described in the available ultrastructural studies in Rubiaceae (Hansson and El-Ghazaly, 2000; El-Ghazaly et al, 2001; Kuang and Liao, 2015). …”
Section: Discussionmentioning
confidence: 58%
“…Other studies, using absolutely different approaches and species Kong and JIA 2004;Kuang and Liao 2015;Qiu et al 2009;Wei et al 2015), consistently showed a clearly cytoplasmic signal, which counts in favor of this notion, too. Thus, we can assume that in in vivo microspores, the signal we observed corresponded to cytosolic Ca 2+ .…”
Section: Calcium Distribution In Non-induced In Vitro Cultured Cellsmentioning
confidence: 78%
“…In lettuce and oil tea, a progressive increase during microsporogenesis, a decrease during vacuolation, a second increase in young pollen grains, and a final decrease in mature pollen was described (Qiu et al 2009). In Uncaria hirsuta, calcium precipitates increased as microsporogenesis proceeded, with a peak in bicellular pollen and a decrease in mature pollen (Kuang and Liao 2015). In tobacco, calcium was detected in the cytoplasm and nucleus of vacuolated microspores and bicellular pollen, decreasing at late pollen stages ).…”
Section: B Napus Shows a Particular Calcium Dynamics During In Vivo mentioning
confidence: 95%
See 2 more Smart Citations